Tipologi Bentuk Arsitektur Masjid di Kota Kendari Pada Era Modern - La Ode Arjuna Pratama; Nur Ayin; La Pande Jurumai (LP3M Universitas Muhammadiyah Kendari, 2022)
The rapid development in the city of Kendari has certainly greatly influenced many things, including in the field of architecture. And one of the developments in the field of architecture is the many innovations related to the design of mosques in the city of Kendari so that it is no longer monotonous. Some mosques in Kendari have even implemented modern principles. The purpose of this research is to identify and obtain the typology of mosques in Kendari so that in the future it can be used as a reference for designers of modern mosques in the future. The research method used is descriptive-qualitative method through typology analysis of mosque buildings which are considered to represent modern mosque buildings in the city of Kendari. The research resulted in a typology of modern mosque buildings in Kendari city as a form of development of mosque architecture in the modern era but without eliminating the Islamic impression which later can become a reference in designing modern mosques, especially in Kendari city